Prognosis of pulmonary embolism associated with syncope: a prospective cohort with the pulmonary embolism registry of Bogodogo university hospital /Burkina Faso - Taryètba Andre Arthur Seghda; Anna Tall/Thiam; Dangwe Temoua Naibe; Georges Rosa Christian Millogo; Abou Coulibaly; Kadari Cissé; Peggy Ouédraogo/Segda; Martin Wendlassida Nacanabo; Djeme Claudine Dah; Mireille Abouga/Loya; Laurence Flork; Nobila Valentin Yameogo; et al. (BMC Pulmonary Medicine)
Abstract Background The prognosis value of syncope in pulmonary embolism remains uncertain. Our aim in this study is to investigate this question. Materials and methods This was a prospective, single-center cohort study of pulmonary embolism from March 1, 2017 to June 31, 2022. Patients were subdivided into two groups according to whether or not they had syncope prior to being hospitalized: syncope (+) vs. syncope (-). Our study analysis aimed at identifying factors associated with the occurrence of syncope. Thereafter, it focused on determining whether syncope was an independent risk factor by using logistic regression that was specific to in-hospital death. Results Four hundred and fifty-one patients were included in the study, including 66 with syncope prior to hospitalization. The prevalence of this symptom during pulmonary embolism was of 14.63%. The variables associated with the occurrence of syncope were presence of proximal localization of the thrombus in pulmonary arteries, significant pulmonary hypertension, dilatation of the right heart chambers and a high severity index. Mortality in the syncope (+) group was significantly higher (24% vs. 9%; OR = 3,2 p < 0.001) in univariate analysis. After regression that was specific to in-hospital death, syncope was not found to be an independent death factor (OR = 1.03 [0.44; 2.42]; p = 0.60). Conclusion Our study shows that syncope is not an independent risk factor for death in PE. It is, however, associated with vulnerable conditions that place patients at high risk of early death.